Additive manufacturing of corrosion-resistant maraging steel M789 by directed energy deposition - Lek, Yung Zhen (2023)
Conventional maraging steels feature a combination of high strength and toughness, but they often suffer from low corrosion resistance. Hence, maraging steel M789 was developed to alleviate this issue while maintaining its strength. Most studies of maraging steels processed by additive manufacturing (AM) focus on utilizing laser powder bed fusion (LPBF). However, the research in laser-directed energy deposition (L-DED) fabrication of corrosion-resistant maraging steels is limited. The different cooling rates experienced by materials during L-DED and LPBF processing give rise to differing microstructures and mechanical properties. In this study, the L-DED process was adopted to manufacture nearly-fully dense M789 parts, which were subsequently subjected to direct aging and solutionizing + aging heat treatments. Electron backscatter diffraction (EBSD) analysis reveals a martensitic structure in both as-fabricated and heat-treated samples with the presence of austenite in the as-fabricated and directly aged samples. Scanning transmission electron microscopy (STEM) and transmission Kikuchi diffraction (TKD) reveal the presence of Ti- and Al-rich precipitates within the martensites after the solution and aging treatment, suggesting that Orowan looping around precipitates, grain boundary strengthening, and solid solution strengthening are responsible for the high yield strength of L-DED M789. Besides, the as-fabricated alloy shows higher pitting potential than solutioned and aged sample. This work serves as a guidance for the fabrication of corrosion-resistant maraging steels by L-DED and accelerate the implementation of maraging steels for marine and offshore applications.